The new French 2010 Rabbit Hemorrhagic Disease Virus causes an RHD-like disease in the Sardinian Cape hare (Lepus capensis mediterraneus) - Puggioni, Giantonella; Cavadini, Patrizia; Maestrale, Caterina; Scivoli, Rosario; Botti, Giuliana; Ligios, Ciriaco; Le Gall-Reculé, Ghislaine; Lavazza, Antonio; Capucci, Lorenzo (Veterinary research (Paris), 2013)
Lagovirus is an emerging genus of Caliciviridae , which includes the Rabbit Hemorrhagic Disease Virus (RHDV) of rabbits and the European brown hare syndrome virus (EBHSV) of hares that cause lethal hepatitis. In 2010, a new RHDV related virus (RHDV2) with a unique genetic and antigenic profile and lower virulence was identified in France in rabbits. Here we report the identification of RHDV2 as the cause in Sardinia of several outbreaks of acute hepatitis in rabbits and Cape hare ( Lepus capensis mediterraneus ). This is the first account of a lagovirus that causes fatal hepatitis in both rabbits and hares.